Growth of tomato seedlings (Solanum lycopersicum L.) treated with vermicompost humate - Chiquito-Contreras, Roberto Gregorio; Reyes-Pérez, Juan José; Troyo-Diéguez, Enrique; Rueda-Puente, Edgar Omar; Torres-Rodríguez, Juan Antonio; Murillo-Amador, Bernardo (Revista Mexicana de Ciencias Agrícolas, 2018)
The humate of vermicompost is a stimulant that improves the quality and productivity of crops and allows the total or partial elimination of chemical fertilizers, contributing to organic, ecological and sustainable agriculture. The objective of this study was to evaluate the effect of different concentrations of vermicompost humates (1/10, 1/20, 1/30 v/v and a control-distilled water-) on the growth of Solanum lycopersicum seedlings grown on affected soils by salinity. The experiment was carried out using a completely randomized design with four repetitions per treatment of 40 seedlings each. At 24 days after transplantation, height of seedlings, stem diameter, number of leaves, fresh and dry weight of aerial part and root were measured. The results showed significant differences between treatments and all the variables showed higher values ​​in the dilution of 1/30 (v/v), followed by the dilutions 1/20 and 1/10, showing lower values ​​in the control. The percentage value of increase in the dilution of 1/30 with respect to the control was 61, 68, 63, 50, 19, 30, 56 and 27 for height, stem diameter, root length, number of leaves, fresh weight of root, dry weight of root, fresh weight of aerial part and dry weight of aerial part, respectively.
Keywords: height, fresh weight, dry weight, salinity.